Niger : Staff Report for the 2004 Article IV Consultation, Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of a Performance Criterion. (IMF Staff Country Reports; Country Report, 2004)
This paper focuses on Niger's 2004 Article IV Consultation, Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion. Niger's macroeconomic performance has been satisfactory in 2002 and 2003, notwithstanding the adverse impact of the crisis in Cote d'Ivoire and large fluctuations in agricultural output owing to uneven rainfalls. Real GDP growth is estimated to have increased to 5.3 percent in 2003, from 3.0 percent in 2002, owing to a bumper crop made possible by favorable weather conditions.